IMPLEMENTASI KEBIJAKAN PENGADAAN BARANG/JASA PEMERINTAH - ., Sularno (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
The phenomenon that made into the object of research is the implementation ofthe procurement of goods/services of government in Karimun. The researchobjective was to discuss the implementation of the procurement of goods/services; discusses the factors that determine the effectiveness, efficiency andaccountability in the implementation of the procurement of goods/services; andobtaining the right policy implementation model for conducting procurement ofgovernment goods/services. The study used a qualitative approach. Determinationinformant as much as 7 informant research study using purposive samplingtechnique. Secondary data collection using literature study and study documents.Primary data collection using interviews and observation techniques. The dataanalysis using descriptive analysis with triangulation approach. Results of thestudy are the following, Implementation of the procurement of goods/services inKarimun Regency Government is implementing Karimun Regent RegulationNumber 31 Year 2012 on the Establishment of Procurement Services UnitGoods/Services Regional Governments Karimun. Implementation of procurementpolicy in question is an activity to obtain goods/services by SKPD that the processstarts from planning until completion of all activities need to obtaingoods/services. The procurement of goods/services are guided by the PresidentialDecree Number 54 Year 2010 concerning Procurement of GovernmentGoods/Services as well as regulation changes, the last Presidential DecreeNumber 172 Year 2014 on the Amendment to the three Presidential DecreeNumber 54 of 2010. The implementation of the procurement of goods/services ofgovernment in Karimun not optimal because there are still weaknesses incommunication management procurement of goods/services. The factors thatdetermine the effectiveness, efficiency and accountability in the procurement ofgovernment goods/services in Karimun is communication, resources, dispositionapparatus attitudes and bureaucratic structure. Among the four factors, thecommunication in the process of implementation of the policy is a factor that mostdetermines the effectiveness, efficiency and accountability in the procurement ofgovernment goods / services in Karimun.Keywords: Policy Implementation, Government, Goods /ServicesProcurementÂ